Internalisasi Nilai Islam Budaya Organisasi Madrasah: Implikasinya Terhadap Iklim Kerja Guru Di Man 1 Karanganyar - Haryati Haryati; Ari Hikmawati (El-Mudarris: Jurnal Manajemen Pendidikan dan Kepemimpinan Sekolah, 2026)
This study aims to analyze the process of internalizing Islamic values within the organizational culture of madrasah and its impact on the working climate of teachers at MAN 1 Karanganyar. A qualitative approach with a case study design was employed to capture the depth and contextual nuances of the phenomenon under investigation. Data were collected through in-depth interviews with the principal, vice principals, and teachers; participant observation of daily institutional activities; and systematic document analysis. Data analysis followed the Miles, Huberman, and Saldaña interactive model, encompassing the stages of data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation to strengthen the credibility of the findings. The findings reveal that the internalization of Islamic values including values of worship (ibadah), honesty (shidq), responsibility (amanah), and brotherhood (ukhuwah) takes place through three primary mechanisms: habituation (pembiasaan), leadership modeling (uswah hasanah), and structured religious programs embedded within the institutional routine. These values collectively shape a distinctive organizational culture that exerts a positive impact on the teachers' working climate, as evidenced by increased levels of mutual trust, social solidarity, professional motivation, and overall job satisfaction among teaching staff. This study affirms that madrasah, as an Islamic educational institution, possesses a unique and strategic capacity to cultivate a conducive and harmonious working environment grounded in an Islamic value foundation, with significant implications for educational management policy and practice.